2012
DOI: 10.1016/j.nlm.2011.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-(1–7)/Mas axis integrity is required for the expression of object recognition memory

Abstract: It has been shown that the brain has its own intrinsic renin-angiotensin system (RAS) and angiotensin-(1-7) (Ang-(1-7)) is particularly interesting, because it appears to counterbalance most of the Ang II effects. Ang-(1-7) exerts its biological function through activation of the G-protein-coupled receptor Mas. Interestingly, hippocampus is one of the regions with higher expression of Mas. However, the role of Ang-(1-7)/Mas axis in hippocampus-dependent memories is still poorly understood. Here we demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 100 publications
1
51
0
2
Order By: Relevance
“…Ang-(1-7) may modulate other responses, including inflammation, reproduction, neuroprotection, learning and memory, anxiety and depression [8,9,12,[32][33][34]. Our present results showed that anxiety-type behaviour in TGRs exposed to the EPM test can be attenuated by ICV administration of Ang- (1-7).…”
Section: Discussionsupporting
confidence: 57%
“…Ang-(1-7) may modulate other responses, including inflammation, reproduction, neuroprotection, learning and memory, anxiety and depression [8,9,12,[32][33][34]. Our present results showed that anxiety-type behaviour in TGRs exposed to the EPM test can be attenuated by ICV administration of Ang- (1-7).…”
Section: Discussionsupporting
confidence: 57%
“…Surprisingly however, only insignificant improvements in the hippocampus-dependent spatial learning were observed in Mas-KO mice (Walther et al, 1998(Walther et al, , 2000a. In contrast, object recognition memory, another hippocampusdependent behavior, was impaired in these animals (Lazaroni et al, 2012), confirming an important but yet elusive role of Mas in hippocampal functions that is not linked to its electrophysiologic actions. However, it may be explained by the role of Mas in neuronal NO generation, which is also involved in memory formation (Yang et al, 2011).…”
Section: F Mas In Behaviormentioning
confidence: 84%
“…Ang-(1-7) not only participates in BP or baroreflex regulation in the brain, but has been shown to improve object recognition memory function [52]. Furthermore, central administration of Ang-(1-7) induces anxiolytic-like effects and decreased oxidative stress in the amygdale of rats [53].…”
Section: Beyond the Brain Effects Of Ang-(1-7) On Blood Pressurementioning
confidence: 99%